A displacement correlation method for stress intensity factor extraction from 3D fractures in anisotropic materials. (December 2021) - Mazurowski, B.; O'Hara, P.; Gupta, P.; Duarte, C.A.
Abstract: A numerical method to extract stress intensity factors (SIFs) from 3D fractures in anisotropic materials is presented. The formulation of a displacement correlation method that is valid for linear elastic materials with arbitrary symmetry in their elastic properties is given in detail. An algorithm for the numerical implementation of the method is also given. The methodology can take an approximate displacement field from any numerical method as input to the extraction process. However, to return accurate stress intensity factors an accurate numerical displacement field is required. In this work, this is provided by a Generalized Finite Element Method. Several verification problems show that the anisotropic displacement correlation method is robust and can extract accurate SIFs. The methodology is used in a parametric study of crack–crack interactions in a high-strength aluminum alloy to demonstrate a practical application. More than 200 simulations are run using the Generalized Finite Element Method, which are largely able to be scripted and ran without user intervention after one simulation is set up. Highlights: Efficient SIF extraction from 3D fractures in arbitrarily anisotropic materials. Isotropic singular enrichments adequate for accurate SIFs in anisotropic materials. Extraction method verified for 3D cracks and crack–crack interactions. Little user intervention needed for parametric study of crack–crack interaction.